SCIENTIFIC DIRECTION OF INTEGRATED RESEARCH OF EDUCATION – OSVITOLOGIYA - Ogneviuk, Viktor; Sysoieva, Svitlana (Continuing Professional Education: Theory and Practice, 2019)
The essence of the new scientific approach to the study of the integrated sphere of education – osvitologiya is disclosed in the article; the changes of the meaning of the notion “education” are analyzed; the objective factors of the interconnections and interdependences strengthening of the modern society and education development; the main points of the osvitologiya’s conception are formulated; the philosophical and pedagogical sources of its forming; the object and the subject of the osvitologiya, the tasks, that face with the osvitologiya as the independent science; it is defined the main stages of the osvitologiya development, the areas of the osvitological training and osvitological researches, that are directed to the overcoming of the society’s demands incompatibilities to the sphere of education with real condition of its development.